Specifications for Building a Parametric Model in Digital Architectural Designs (Journal of University of Babylon for Engineering Sciences, 2018)
The construction of parametric model is an important stage in the digital design process in general and in the parametric design process in particular. The parametric model allows the designer to make changes and reshape the geometry without erasing and redrawing. It also helps to explore design alternatives as it provides a level of flexibility to be continuously evaluated, revised and updated when adding or altering different components within the same parametric model structure.The research problem has been identified, as there is no clear definition of the specifications of constructing a parametric model in the contemporary digital architectural designs. Therefore, the objective of the research is to put forward a theoretical framework that defines clearly the specifications of building a parametric model. The framework describes the specifications using the following issues: the timing of constructing the parametric model, the knowledge employed in the construction of parametric model, the methods of constructing and revising a parametric model, The place where a parametric model is applied, and finally the number of parametric models within a design. The framework has been applied to six international projects adopting a parametric design approach. The results showed that employing parametric modeling mostly starts at the development stage of design and continues in the detailing and manufacturing stages, the adoption of ill-defined knowledge, the definition of design variables in terms of quantitative and qualitative characteristics, and using one parametric model shared among multiple design disciplines.